Serum uric acid and risk of prehypertension: a dose–response meta-analysis of 17 observational studies of approximately 79 thousand participants. Issue 2 (7th February 2022) - Liu, Leilei; Zhang, Xiao; Li, Quanman; Qie, Ranran; Han, Minghui; Zhan, Shaohui; Zhang, Juntao; Zhang, Linyuan; Zhang, Cailiang; Hong, Feng
Abstract: Background: Studies examining the association between levels of serum uric acid (SUA) and risk of prehypertension still remained controversial conclusions. Also, a quantitative assessment of the dose–response association between them has not been reported. We aimed to quantitatively evaluate risk of prehypertension with levels of SUA based on observational study. Methods: We searched the PubMed, Embase, and Web of Science databases up to December 3, 2019 for relevant studies. Pooled relative risks (RRs) and 95% confidence intervals (CIs) were calculated using random-effects models. The possible linear or non-linear SUA–prehypertension association was modelled by restricted cubic splines. Results: We included 17 articles (17 studies) with a total of 79, 358 participants and 34, 591 cases of prehypertension. Compared with lowest levels of SUA, risk of prehypertension increased 46% (RR 1.46, 95% CI 1.28–1.66) for highest levels of SUA. For per 1 mg/dL increment in levels of SUA, risk of prehypertension increased by 12% (RR 1.12, 95% CI 1.08–1.17). Also, we found evidence of a linear SUA–prehypertension association ( P non-linearity =.368). Conclusion: Elevated levels of SUA may be associated with increased risk of prehypertension. Present findings provide the evidence that lowering levels of SUA should be suggested in order to reduce the risk of prehypertension. More longitudinal and intervention studies are needed to clarify the optimal protective levels and whether reducing levels of SUA could prevent or control prehypertension and the progression of prehypertension to hypertension.